Computer Analysis of Damage Development in Rectangular Plates - Białkiewicz, J.; Mika, P. (Engineering Transactions, 1995)
A numerical analysis of the time-dependent rupture of a plate of moderate thickness is presented. The solutions focus on the time and localisation of appearance of the first macroscopic cracks as well as on the mode of rupture front propagation to the instant of failure. The damage development is coupled with the variation of the plate thickness.